Spin waves in the B-phase of superfluid ³He in confined cylindrical geometry - Benningshof, O.W.B.; Jochemsen, R. (Физика низких температур, 2013)
We describe experiments on superfluid ³He in a cylinder of 1 mm in diameter. This geometry causes the preferred
orientation of the n-vector in the superfluid B-phase to be locally different, resulting in a curved configuration
across the sample. Exclusive to our experiment is the observation that we succeeded in obtaining a texture
which is metastable and unchanged in our pressure and temperature ranges, most likely because the experiment
is performed at low pressures and low magnetic fields. As this texture can be considered as a potential for spin
waves, we had the unique opportunity to study spin waves for several pressures in exactly the same texture. Our
geometry causes this texture potential to be nearly quadratic, allowing an analytic solution of the theory which
can be compared to our experimental results. As predicted we find the intensities of all spin wave modes more or
less equal. Increasing the pressure shows a gradual increase in the number of spin wave modes in our cell. Finally
we were able to cause a transition from the metastable to the predicted stable texture, concluding unexpectedly
that the metastable texture is realized if the growing (or cooling) speed is sufficiently slow.